2009
DOI: 10.1002/prot.22377
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of formation of the C‐terminal β‐hairpin of the B3 domain of the immunoglobulin binding protein G from Streptococcus. II. Interplay of local backbone conformational dynamics and long‐range hydrophobic interactions in hairpin formation

Abstract: Two peptides, corresponding to the turn region of the C-terminal β-hairpin of the B3 domain of the immunoglobulin binding protein G from Streptoccocus, consisting of residues 51-56 ] and 50-57 ], respectively, were studied by CD and NMR spectroscopy at various temperatures and by differential scanning calorimetry. Our results show that the part of the sequence corresponding to the β-turn in the native structure (DDATKT) of the B3 domain forms bent conformations similar to those observed in the native protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
44
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 89 publications
12
44
3
Order By: Relevance
“…Using this approach, as the backbone H-bond interactions were defined solely as enthalpic constraints, our results show that backbone H-bonds only have a minor effect on the sigmoidal behavior (cooperative behavior) because of their small free energy contribution. This result is consistent with Scheraga and his coworkers, who pointed out that no clear evidence supports the presence of backbone H-bonds in non-turn regions [8,66,67,[80][81][82][83][84]. In other words, the backbone H-bond interaction may not contribute as much as expected in the cooperative formation of β-hairpins but may play only a structural as well as energetic constraint in modulation of the cooperative system [see Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Using this approach, as the backbone H-bond interactions were defined solely as enthalpic constraints, our results show that backbone H-bonds only have a minor effect on the sigmoidal behavior (cooperative behavior) because of their small free energy contribution. This result is consistent with Scheraga and his coworkers, who pointed out that no clear evidence supports the presence of backbone H-bonds in non-turn regions [8,66,67,[80][81][82][83][84]. In other words, the backbone H-bond interaction may not contribute as much as expected in the cooperative formation of β-hairpins but may play only a structural as well as energetic constraint in modulation of the cooperative system [see Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In our study of the 20-residue peptide, we observed a similar situation of long-range interactions between hydrophobic residues located far from the turn region and an absence of H N (i) – H N (i+1) interactions within the turn region35. The hydrophobic interaction (between Val47 and Val59) observed in the IG(28-61) fragment at 313 K is a non-native one, as was often observed for shorter β-hairpin fragments studied in our previous work [between the “1 st pair” (Tyr50 – Phe57)22,33,34 and the “2 nd pair” (Trp48 – Val59) of hydrophobic residues] 22,35. This means that hydrophobic interactions, as well as any long-range interactions, which stabilize the C-terminal β-hairpin structure, are very dynamic and their pattern is very sensitive to the length of the peptide under investigation.…”
Section: Resultsmentioning
confidence: 63%
“…On the other hand, for the 20-residue peptide studied in our previous work35, we showed that none of the amide protons possessed small temperature coefficients. The results of NMR measurements of peptides of different length show that amide protons with low temperature coefficients are always observed in the turn region22,33-34; however, in some cases, the presence of the turn structure (detected by ROE connectivities) was not associated with low-temperature-coefficient amide protons35. Such an observation could lead to the conclusion that possible hydrogen bonds in the turn region are rather induced by the general shape of the polypeptide chain in the turn region, but are not the interaction that creates the turn of the polypeptide chain22,22-35.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations